Achieving Large Volumetric Gas Storage Capacity in Metal-Organic Frameworks by Kinetic Trapping: A Case Study of Xenon Loading in MFU-4 - Bunzen, Hana; Kolbe, Felicitas; Kalytta-Mewes, Andreas; Sastre, German; Brunner, Eike; Volkmer, Dirk (Journal of the American Chemical Society, 2018)
One of the main problems of gas storage in porous materials is that many molecules of interest adsorb too weakly to be retained effectively. To enhance gas storage in metal-organic frameworks (MOFs), we propose the use of kinetic trapping, i.e., a process where the guest gas is captured in the voids at loading conditions and not released immediately at normal conditions. In this approach, the diffusion-limiting pore size and the framework flexibility have to be matched to the gas, requiring flexible pore apertures to be smaller than the van der Waals diameter of the trapped guest. We selected the Metal-Organic Framework Ulm University-4 (MFU-4) with a pore aperture of 2.52 Å as a model coordination framework and used it for storage of xenon (with van der Waals diameter of 4.4 Å). Although xenon atoms are substantially larger than the MOF pore aperture, MFU-4 could be loaded with xenon by applying moderately high gas pressures. This is demonstrated to be due to the pore flexibility as confirmed by computational studies. The xenon loading could be tuned (from 0 wt % to more than 44.5 wt %) by changing the loading parameters such as pressure, temperature, and time, and the xenon atoms remained inside the pores upon exposing the material to air atmosphere at room temperature. To understand the material behavior, TGA, XRPD, and 129Xe NMR spectroscopy and computational studies were carried out.
CRIS-Team Scopus Importer:2022-04-14